INFFLUENCE OF STUDENTS’ ENGAGEMENT IN APPRENTICESHIP ON THEIR LEARNING READINESS AND ACADEMIC PERFORMANCE IN MATHEMATICS - Omotayo, Stephen Akinyemi (African Journal of Behavioural and Scale Development Research, 2024)
Students’ engagement in apprenticeship is becoming a general phenomenon in Nigeria, especially among low income earners. This has been attributed to many factors which include the fear of the alarming rate of unemployment among graduates. It was also seen as way of mitigating the impact of economic hardship experienced by ordinary citizens. The consequence of this practice on students’ academic performance has generated mixed feelings among researchers. Sequel to this, the present study sought to establish the level of secondary school students’ engagement in apprenticeship and how it affects their learning readiness and academic performance in mathematics. The study was a survey type, which targeted all secondary school students in Ibadan. Multistage sampling methods were adopted to select the 600 secondary school students who participated in the study. The findings revealed that more than half of the students 68% were engaged in apprenticeship and there exist a significant inverse correlation between students level of engagement in apprenticeship and their learning readiness (r = -.133, p < 0.05). Also, the finding revealed that students who do not engaged in apprenticeship ( = 16.01 SD = 1.07) performed better than those who were engaged ( = 12.92, SD =3.22), t(598) = -11.226, p < 0.05.The study further shows that the practice is more common in the less city and there is no gender disparity. Parents should understand the appropriate time to engage their children in apprenticeship and closely monitor their activities. Key Word: Apprenticeship, Engagement, Learning Readiness, Performance